2017
DOI: 10.3791/55355
|View full text |Cite
|
Sign up to set email alerts
|

Defined and Scalable Generation of Hepatocyte-like Cells from Human Pluripotent Stem Cells

Abstract: Human pluripotent stem cells (hPSCs) possess great value for biomedical research. hPSCs can be scaled and differentiated to all cell types found in the human body. The differentiation of hPSCs to human hepatocyte-like cells (HLCs) has been extensively studied, and efficient differentiation protocols have been established. The combination of extracellular matrix and biological stimuli, including growth factors, cytokines, and small molecules, have made it possible to generate HLCs that resemble primary human he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 27 publications
0
61
0
Order By: Relevance
“…We previously reported that the high energy substrate cocktail LPO promotes intracellular lipid accumulation in HLCs [17] although it was not known whether LPO promotes lipid droplet biogenesis or increased accumulation of lipids within existing droplets. Stem cell derived HLCs were differentiated and characterised as before [18] (Figure 1A). Analysis of gene expression using RT-qPCR showed increased expression of transcripts for PLIN2, PLIN4, and PLIN5, which are typically associated with intracellular lipid droplet membranes, suggesting an increase in lipid droplet size (Figure 1B-D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the high energy substrate cocktail LPO promotes intracellular lipid accumulation in HLCs [17] although it was not known whether LPO promotes lipid droplet biogenesis or increased accumulation of lipids within existing droplets. Stem cell derived HLCs were differentiated and characterised as before [18] (Figure 1A). Analysis of gene expression using RT-qPCR showed increased expression of transcripts for PLIN2, PLIN4, and PLIN5, which are typically associated with intracellular lipid droplet membranes, suggesting an increase in lipid droplet size (Figure 1B-D).…”
Section: Resultsmentioning
confidence: 99%
“…Human female H9 pluripotent stem cells (PSCs) were differentiated to hepatocyte-like cells (HLCs) as previously described [18]. HLCs were cultured in a 96-well format for measurements of lipid accumulation and in a 6-well format for all other analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The generation of human liver cells de novo has gained traction thanks to the development of protocols for the differentiation of hPSCs. Hepatocyte‐like cells have been derived from hPSCs in two‐dimensional tissue culture settings by means of directed differentiation using Activin A, and combinations of FGF4, hepatocyte growth factor (HGF), oncostatin M (OSM), and dexamethasone (Dex) . The cells obtained following those protocols possess characteristics of immature, fetal hepatocytes, and fail to maintain the hepatocyte phenotype, limiting their potential for therapeutic or clinical applications .…”
Section: Liver Organoid Damage and Fibrosismentioning
confidence: 99%
“…Hepatocyte-like cells have been derived from hPSCs in two-dimensional tissue culture settings by means of directed differentiation using Activin A, and combinations of FGF4, hepatocyte growth factor (HGF), oncostatin M (OSM), and dexamethasone (Dex). [48][49][50][51][52][53][54] The cells obtained following those protocols possess characteristics of immature, fetal hepatocytes, and fail to maintain the hepatocyte phenotype, limiting their potential for therapeutic or clinical applications. 55 Alternative protocols for the development of human liver tissues relied on matrix or scaffolds for the formation of 3D aggregates with or without inclusion of other cell types.…”
Section: Liver Organoid Damage and Fibrosismentioning
confidence: 99%
“…The ability of human pluripotent stem cells (hPSCs) to self-renew, whilst retaining pluripotency, provides an opportunity to produce human cell types and tissues on demand. hPSCs have been efficiently differentiated into hepatocyte-like cells (HLCs) using two-dimensional (2D) adherent culture systems 1,2,3,4,5,6,7,8,9,10 . These systems have been used to successfully model monogenic disease, virus lifecycle, drug induced liver injury (DILI), fetal exposure to toxins and non-alcoholic fatty liver disease (NAFLD) 11,12,13,14,15 .…”
Section: Introductionmentioning
confidence: 99%